Alveolar Crestal Approach for Maxillary Sinus Membrane Elevation with <4 mm of Residual Bone Height: A Case Report - Jae Won Jang; Hee-Yung Chang; Sung-Hee Pi; Yoon-Sang Kim; Hyung-Keun You (International Journal of Dentistry)
Introduction. For maxillary sinus membrane elevation (MSME), the lateral window approach and crestal approach are available, and high success rates have been achieved with low residual bone height as a development of technology. Objective. To evaluate MSME using the crestal approach with a rotary-grind bur (RGB (including reamer or sinus bur)) in patients with residual bone height of <4 mm. Materials and Methods. Ten implants were placed in 10 patients with residual bone height of <4 mm, by sinus elevation using an RGB. The implant stability quotient (ISQ) was measured immediately after implant placement (ISQ 1) and before taking impression for the final prosthesis (ISQ 2). The extent of marginal bone loss was measured on periapical radiographs. Results. The mean residual bone height before implant placement was 3.41 ± 0.53 mm; no complications, including membrane perforation, severe postoperative pain, or discomfort, occurred either during or after surgery. The mean ISQ 1 was 63.4 ± 12.1, whereas the mean ISQ 2 was 77.6 ± 5.8. The mean marginal bone resorption was 0.23 ± 0.18 mm on periapical radiographs. Conclusions. MSME using the crestal approach with an RGB is a reliable technique for implant placement in sites where available bone is insufficient.